THE ROLE OF STRATEGIC MANAGEMENT IN BUILDING COMPETITIVE ISLAMIC EDUCATION INSTITUTIONS - Yudi Ardian Rahman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
Education is one of the crucial aspects of life, especially along with the times. However, the implementation of education in Indonesia is still not optimal. Therefore, improvements in education management are needed. The purpose of writing this work is to understand strategic management, strategic management in the context of Islamic education, and factors that influence the strategic management of Islamic education. This writing uses the literature study method. The results of the literature study show that strategic management is a science related to the formulation, implementation, and evaluation of cross-functional decisions that enable organizations to achieve their goals. Meanwhile, strategic management of Islamic education is a structured activity that includes planning, organizing, staffing, and supervising in all elements of the implementation of Islamic education. In practice, there are several factors that affect the strategic management of Islamic education, including a lack of direction in strategy, failure in planning, and too much focus on processes. Keywords: Management, Strategic, Islamic Education Institution